Factors Associated With Extended Length of Stay and 90-Day Readmission Rates Following ACDF. Issue 3 (May 2020) - Dial, Brian L.; Esposito, Valentine R.; Danilkowicz, Richard; O'Donnell, Jeffrey; Sugarman, Barrie; Blizzard, Daniel J.; Erickson, Melissa E.
Study Design: Retrospective. Objective: Identify patient risk factors for extended length of stay (LOS) and 90-day hospital readmissions following elective anterior cervical discectomy and fusion (ACDF). Methods: Included ACDF patients from 2013 to 2017 at a single institution. Eligible patients were subset into LOS <2 and LOS ≥2 days, and no 90-day hospital readmission and yes 90-day hospital readmission. Patient and surgical factors were compared between the LOS and readmission groups. Multivariable logistic regression analysis was utilized to determine the association of independent factors with LOS and 90-day readmission rates. Results: Our sample included 1896 patients; 265 (14%) had LOS ≥2 days, and 121 (6.4%) had a readmission within 90 days of surgery. Patient and surgical factors associated with LOS included patient age ≥65 years (odds ratio [OR] 1.72, 95% confidence interval [CI] 1.15-2.56), marriage (OR 0.57, 95% CI 0.43-0.79), private health insurance (OR 0.28, 95% CI 0.15-0.50), American Society of Anesthesiologists (ASA) score (OR 1.52, 95% CI 1.12-1.86), African American race (OR 1.95, 95% CI 1.38-2.72), and harvesting iliac crest autograft (OR 4.94, 95% CI 2.31-10.8). Patient and surgical factors associated with 90-day hospital readmission included ASA score (OR 1.81, 95% CI 1.32-2.49), length of surgery (OR 1.002, 95% CI 1.001-1.004), and radiculopathy as indication for surgery (OR 0.60, 95% CI 0.39-0.96). Conclusions: Extended LOS and 90-day hospital readmissions may lead to poorer patient outcomes and increased episode of care costs. Our study identified patient and surgical factors associated with extended LOS and 90-day readmission rates. In general, preoperative patient factors affected these outcomes more than surgical factors.